Sintered polycrystalline cubic boron nitride material
By using a combination technology of high content of cubic boron nitride (cBN) and metal compound particles in tool materials, the problem that the prior art is difficult to maintain high efficiency performance under extreme conditions is solved, and tool materials with high hardness, wear resistance and long life are achieved.
Patent Information
- Application Number
- JP2022516085
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-13
- Filing Date
- 2020-09-10
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-09-10
AI Technical Summary
The prior art is difficult to maintain effective performance under extreme conditions when manufacturing high-performance tool materials, and is highly dependent on key raw materials.
A polycrystalline cubic boron nitride (PCBN) material consisting of cubic boron nitride (cBN) particles is used, and a tool material with high hardness and wear resistance is formed by combining cBN particles with particles of metal compounds such as zirconium and vanadium under high temperature and high pressure.
Tool materials that maintain efficient performance under extreme conditions are achieved, extending the service life of the tool and reducing dependence on key raw materials.
Smart Images

Figure 0007654641000008 
Figure 0007654641000009 
Figure 0007654641000010
Abstract
Description
[Technical field]
[0001] The present invention relates to sintered polycrystalline cubic boron nitride materials and methods for making such materials. [Background technology]
[0002] Polycrystalline superhard materials, such as polycrystalline diamond (PCD) and polycrystalline cubic boron nitride (PCBN), can be used as a wide variety of tools for cutting, turning, drilling or grinding hard or abrasive materials, such as rock, metals, ceramics, composites and wood-containing materials. Abrasive compacts are widely used for cutting, turning, grinding, milling, drilling and other abrasive operations. They usually contain ultrahard abrasive particles dispersed in a second phase matrix. The matrix can be metal or ceramic or cermet. The ultrahard abrasive particles can be diamond, cubic boron nitride (cBN), silicon carbide or silicon nitride, etc. These particles can bond together to form a polycrystalline mass during the high pressure and high temperature compact manufacturing process, or bond through a matrix of the second phase material(s) to form a sintered polycrystalline body. Such materials are usually known as polycrystalline diamond or polycrystalline cubic boron nitride, where they contain diamond or cBN, respectively, as the ultrahard abrasive. No. 4,334,928 teaches a sintered body for use as a tool consisting essentially of 20-80 volume percent cubic boron nitride and the balance being a matrix of at least one matrix composite selected from the group consisting of carbides, nitrides, carbonitrides, borides and silicides of periodic table IVa or Va transition metals, mixtures thereof and solid solution compounds thereof. The matrix forms a continuous bonded structure in the sintered body with the high pressure boron nitride interspersed within the continuous matrix. All of the methods outlined in this patent require combining the desired materials using mechanical grinding / mixing techniques such as ball milling, mortars, etc. Sintered polycrystalline bodies can be "back-machined" by molding them on a substrate. Cemented carbide can be used to form a suitable substrate, for example, formed from dispersed carbide particles in a cobalt matrix by mixing tungsten carbide particles / grains with cobalt together and then heating to solidify. To form a cutting element with a layer of superhard material such as PCD or PCBN, diamond particles or grains or CBN grains are placed adjacent to the cemented carbide body in a heat-resistant metal housing such as a niobium housing and subjected to high pressure and high temperature so that intergranular bonding occurs between the diamond grains or CBN grains, forming a polycrystalline superhard diamond or polycrystalline CBN layer.
[0003] In some cases, the substrate is fully cured prior to bonding to the ultra-hard material layer, while in other cases the substrate may be green (not fully cured material). In the latter case, the substrate may be fully cured during the HTHP sintering process. The substrate may be in powder form and may solidify during the sintering process used to sinter the ultra-hard material layer. FIG. 1 illustrates an exemplary method for producing sintered PCBN material. The following numbering corresponds to that of FIG. 1: S1. Matrix precursor powder is premixed. Examples of matrix precursor powder include carbides and / or nitrides of titanium and aluminum. The typical average particle size of the matrix precursor powder is 1 μm to 10 μm. S2. The matrix precursor powder is heat treated above 1000°C for at least 1 hour to initiate pre-reaction between the matrix precursor particles and form a "cake". S3. The cake is crushed and sieved to obtain the desired particle size fraction. S4. Cubic boron nitride (cBN) particles with an average particle size of 0.5 μm to 15 μm are added to the sieved matrix precursor powder. S5. The resulting mixed powder is ground by ball milling until the matrix precursor powder reaches the desired size (usually 50 nm to 700 nm) and the precursor powder and cBN particles are homogeneously mixed. This process may take several hours and requires grinding media such as tungsten carbide balls. S6. The resulting milled powder is dried under vacuum or reduced pressure at above 60°C to remove the solvent and then conditioned by slowly introducing oxygen into the system to passivate the metal surfaces such as aluminum. S7. The dry powder is sieved to create a pre-composite construct. S8. The precomposite construct is heat treated above 700° C. to remove any adsorbed water or gases. S9. The gas-releasing precomposite construction is incorporated into a capsule suitable for sintering. S10. The capsule is sintered in a high pressure, high temperature (HPHT) process at at least 1250° C. and at least 4 GPa to form a sintered PCBN material.
[0004] Both tungsten (W) and cobalt (Co) are classified as European Critical Raw Materials (CRM). CRMs are raw materials that are considered to be of economic and strategic importance to the European economy. In principle, they have high risks associated with their supply, are vital to key sectors of the European economy such as consumer electronics, environmental technology, automotive, aerospace, defense, health and steel, and moreover, they have no (viable) substitutes. Both tungsten and cobalt are major components of two important classes of hard materials, cemented carbide / WC-Co and PCD / diamond-Co. Summary of the Invention
[0005] It is an object of the present invention to develop a viable alternative material for tooling operations that performs well under extreme conditions. In one aspect of the invention, there is provided a polycrystalline cubic boron nitride (PCBN) material comprising: 30-90 volume % cubic boron nitride (cBN) particles; a matrix material having a content of 10 volume % to 70 volume % of the PCBN material having the cBN particles dispersed therein; the matrix material comprising either a titanium compound and an aluminum compound, or a mixture thereof; the matrix material further comprising precipitates and / or grains comprising zirconium and / or vanadium, and optionally tungsten and / or titanium; said precipitates and / or grains being either substantially spherical, platelet-like or acicular, said precipitates and / or grains having an average maximum linear dimension of 1 μm or less. The precipitates and / or grains may include nitrides, carbides, carbonitrides and / or diborides. Optionally, the zirconium-containing precipitates and / or grains and / or the vanadium-containing precipitates and / or grains comprise between 10% and 25% by volume of the PCBN material. Optionally, the zirconium-containing precipitates and / or grains and / or the vanadium-containing precipitates and / or grains comprise 10% by volume, or 17.5% by volume, or 25% by volume of the PCBN material. The zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains may have an average maximum linear dimension of less than or equal to 0.50 μm. Alternatively, the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains may have an average maximum linear dimension of less than or equal to 0.20 μm. The matrix material may include any of titanium carbonitride, titanium carbide, titanium nitride, titanium diboride, aluminum nitride, and aluminum oxide. The PCBN material may contain 10% to 25% by volume of titanium carbide, TiC, or titanium nitride, TiN. The PCBN material also includes 5% by volume of aluminum, Al, or a compound thereof. Preferably, the PCBN material comprises 60% by volume cubic boron nitride (cBN). In one option, the cBN particles have an average size of between 0.5 μm and 15 μm. Preferably, the PCBN material has a Vickers microhardness of between 26 GPa and 34 GPa.
[0006] In a second aspect of the present invention, there is provided a method for producing polycrystalline cubic boron nitride (PCBN), a material, the method comprising: grinding together the following precursor powders: Cubic boron nitride (cBN), vanadium-containing powder and / or zirconium-containing powder, and A powder containing either aluminum or titanium, compressing the milled precursor powder to form a green compact; sintering the green compact at a temperature of 1800°C to 2300°C and a pressure of 7.0 GPa to 8.5 GPa to form a sintered PCBN material; The sintered PCBN material comprises cubic boron nitride (cBN) particles dispersed in a matrix material comprising, or consisting of, zirconium-containing precipitates and / or vanadium-containing precipitates, and optionally tungsten-containing precipitates and / or titanium-containing precipitates, said precipitates having an average maximum linear dimension of 1 μm or less. One option is a temperature of 1800°C to 1900°C. Optionally, the step of grinding the precursor powders together comprises the following two sub-steps: milling the vanadium-containing powder and / or the zirconium-containing powder for a period of time; adding powder of cubic boron nitride and aluminum and / or titanium containing powder; Milling all the precursor powders together for an additional period of time. The method may further comprise dividing the green compact into portions prior to the sintering step.
[0007] In a third aspect of the invention, a tool comprises a PCBN material according to the first aspect of the invention. Preferably, the tool is a tool for cutting, turning, milling, grinding, drilling, or other abrasive applications. Non-limiting embodiments are hereinafter described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0008] [Figure 1] 1 is a flow diagram of an exemplary method for producing a known sintered PCBN material. [Diagram 2] 1 is a flow diagram showing exemplary manufacturing steps for PCBN material according to the present invention. [Diagram 3] 1 shows scanning electron microscope (SEM) pictures of PCBN TiC reference material sintered at 1800° C. at different magnifications. [Figure 4] SEM images of PCBN ZrN 10 vol% system sintered at 1800℃ at different magnifications. [Diagram 5] SEM images of PCBN ZrN 17.5 vol.% sintered at 1800°C at different magnifications. [Figure 6] SEM images of PCBN ZrN 25% by volume sintered at 1800°C at different magnifications. [Figure 7] SEM images of PCBN VN 25% by volume sintered at 1800°C at different magnifications. [Figure 8] Examples of microstructural features are shown: a) A1, b) A2, c) N1, d) N2, and e) N3. [Figure 9] The SEM photograph of cBN-TiC-VN-Al (60-25-10-5 volume%) sintered at 1750°C is shown. [Figure 10] The SEM photograph of cBN-TiC-VN-Al (60-25-10-5 volume%) sintered at 1850°C is shown. [Figure 11] The SEM photograph of cBN-TiC-VN-Al (60-17.5-17.5-5 volume%) sintered at 1750°C is shown. [Figure 12] A high-magnification SEM photograph of cBN-TiC-VN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1850°C is shown. [Figure 13]The SEM photograph of cBN-TiC-ZrN-Al (60-25-10-5 volume %) sintered at a temperature of 1750°C is shown. [Figure 14] A high-magnification SEM photograph of cBN-TiC-ZrN-Al (60-25-10-5 volume%) sintered at a temperature of 1850°C is shown. [Figure 15] The SEM photograph of cBN-TiC-ZrN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1750°C is shown. [Figure 16] The SEM photograph of cBN-TiC-ZrN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1850°C is shown. [Figure 17] A high-magnification SEM photograph of cBN-TiN-ZrN-Al (60-25-10-5 volume%) sintered at a temperature of 1750°C is shown. [Figure 18] A low-magnification SEM photograph of cBN-TiN-ZrN-Al (60-25-10-5 volume%) sintered at a temperature of 1750°C is shown. [Figure 19] A low-magnification SEM photograph of cBN-TiN-ZrN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1750°C is shown. [Figure 20] A high-magnification SEM photograph of cBN-TiN-ZrN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1850°C is shown. [Figure 21] The SEM photograph of cBN-TiN-VN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1750°C is shown. [Figure 22] The SEM photograph of cBN-TiN-VN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1850°C is shown. [Figure 23] 1 shows an SEM photograph of cBN-ZrN-VN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1750°C. [Figure 24] 1 shows an SEM photograph of cBN-ZrN-VN-Al (60-17.5-17.5-5 volume%) sintered at a temperature of 1850°C. [Diagram 25]1 is a graph showing tool wear (VB life criterion=0.3 mm) versus cutting time machining Caldie hardened steel for a first set of PCBN types. [Figure 26] 13 is a graph showing the variation of tool wear (VB life criterion=0.3 mm) with cutting time machining Caldie hardened steel for a second set of PCBN types. [Figure 27] 1 is a graph showing the variation of tool wear (VB life criterion=0.3 mm) with cutting time for machining Inconel 718 for a first set of PCBN types. [Figure 28] 13 is a graph showing the variation of tool wear (VB life criterion=0.3 mm) with cutting time for machining Inconel 718 for a second set of PCBN types. [Figure 29] 1 is a graph showing Ra as a function of workpiece passes when machining Ovako 677. [Diagram 30] 1 is a graph showing Ra as a function of workpiece passes when machining Ovako 677. [Diagram 31] FIG. 1 is a series of SEM photographs showing tool degradation on all edges of the test grades from 1st to 9th workpiece passes. [Diagram 32] 1 is a series of SEM photographs showing different grades of wear at the end of tool life. [Diagram 33] This is a STEM image of sample V2. [Diagram 34] A further STEM image of sample V2. [Diagram 35] Yet another STEM image of sample V2. [Diagram 36] 13 is a STEM image of additional sample V2. [Figure 37] This is a STEM image of sample Z1. [Figure 38] This is a STEM image of sample Z11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The composition of the materials shown in the SEM photographs above was confirmed using transmission electron microscope (TEM) analysis. 2 is a flow diagram showing exemplary steps. The following numbering corresponds to that of FIG. S1. Precursor powders of zirconium-containing powder and / or vanadium-containing powder, and powders containing carbides and / or nitrides of titanium and aluminum are milled together to form a homogenous mixture and obtain the desired particle size. Precursor powder mixing was performed using ball milling techniques in an organic solvent and drying by rotary evaporation. S2. The milled powders are dry pressed together to form a green compact that has adequate strength for handling during processing. Specifically, after drying, the powders are packed into a soft mold and pressed using a cold isostatic press to compress the powder into a green compact. The compacts are then cut to different heights to be placed into High Pressure High Temperature (HPHT) capsules. S3. The dry pressed green compact is then sintered in a high temperature vacuum heat treatment and HPHT capsule at a temperature of at least 1800°C (e.g., 1800°C, 1900°C, 2000°C, and 2200°C) and a pressure of about 8 GPa for a period of at least 30 seconds. The sintering temperature was calibrated up to 1800° C. using an S-type thermocouple. S4. After sintering, the resulting sintered article is cooled to room temperature. The cooling rate is uncontrolled. Cooling results in the desired precipitation of VN-containing precipitates and / or ZrN-containing precipitates and optional W- and / or Ti-containing precipitates. EXAMPLES
[0010] Table 1 lists all of the PCBN compositions included in this study, along with a TiC reference sample (ie, a sample without ZrN or VN in the binder). [Table 1]
[0011] Visual inspection after sintering Figures 3, 4, 5, 6 and 7 show SEM pictures of different PCBN species sintered at 1800°C. They are all homogeneous. In these images, the color contrast is due to the difference in atomic weight. The cBN component is the lightest and appears as a very dark / black color in these images. The ceramic components (such as VN or ZrN) are seen as grey phases in the SEM images and the heaviest metallic components (such as WC contamination from ball milling) appear as light / white particles. The results revealed that the powder mixing method results in a homogeneous distribution of the cBN and ceramic components.
[0012] Hardness inspection after sintering The next step was to understand the effect of the sintering conditions on the properties of the materials. These materials were tested by indentation using a 1 Kg Vickers indentation method and the hardness results were calculated and are summarized in Table 2. The indentations were made with a Wolpert 572 indenter and the indentations were measured in a SEM to improve accuracy (as the indentations were on the order of 20 microns in size). [Table 2] All sintered pieces had good hardness, with microhardness on the order of 28 GPa, which was considered good for this level of cBN content. A very low hardness would be considered an indication of insufficient sintering / bonding of the material phases. For the same reason, higher hardness values were considered an indication of good sintering. Therefore, hardness was used as a first indicator of optimized sintering conditions.
[0013] Application pre-screening test Next, samples were selected for application pre-screening testing. These samples are shown in Table 3. [Table 3] Further information regarding the composition of the samples selected for application prescreening testing is provided in Table 4 below. [Table 4] The selected species were tested by machining four materials: (1) hardened (HRC 62.1) tool steel Caldie (by Uddeholm); (2) aged (HRC 44.7) superalloy Inconel 718 (trademark); (3) precipitation hardened (HRC 42.7) martensitic stainless steel 17-4PH; and (4) Ovako 677 (Ovatec 677). (1) Testing with Caldie hardened steel Pre-screening tests were carried out with selected PCBN species by machining Caldie hardened steel under the following cutting conditions: surface cutting speed Vc = 120 m / min, feed rate f = 0.1 mm / rev, depth of cut a p =0.3mm, and dry processing conditions. The results are shown in Figures 25 and 26. Referring first to Figure 25, the 5 min reference specimen R1 had a maximum BV=263 μm, but also experienced microfractures at VB=421 μm. Test results show that for this hard turning application, specimen V2, a TiC-VN based PCBN specimen, performed 80-90% better (1.9 times) than the reference material. Referring to FIG. 26, the results show that TiC—ZrN species Z11 performs nearly 90% better than the reference sample, but the other TiC—ZrN species also outperform R1 and R2. This means that for Caldie hard turning applications, the V2 and Z11 grades outperform the high pressure TiC reference material by up to 90% (1.9 times). For this tool geometry (RNGN090300), flank wear (VB) is the main wear criterion and crater formation is negligible, whereas for tools with smaller nose radii, crater wear (KT) can become more dominant. (2) Testing by machining Inconel 718 Pre-screening tests were also carried out using selected PCBN species by machining Inconel 718 under the following cutting conditions: Vc = 250 m / min, f = 0.1 mm / rev, depth of cut ap =0.3mm, and high pressure coolant of 7000kPa (70 bar). The results of the tests, shown in FIG. 27, indicate that the TiC-ZrN-based species Z1 performed slightly better (up to 15%) than both benchmarks, while the VN-based species performed 25% worse. As can be seen from FIG. 28, TiC-ZrN species Z2 and Z11 performed better (up to 20%) than both benchmarks, while Z8 performed equally well. (3) Testing by machining martensitic stainless steel In martensitic stainless steel applications, none of the PCBN types performed better than the baseline material. (4) Testing by machining Ovako 677 hardened steel Testing was performed on a Monforts RNC700 single-turn horizontal lathe and a standard parallel shank tool holder (CCLNL3225). Surface roughness measurements were performed with a Mahr MarSurf M300 surface measurement gauge. Images of wear morphology during testing were generated with an Alicona all-focus optical profilometer. The industry standard PCBN material with 50% cBN by volume, DSC500, was also tested as a standard performance benchmark. Tests were performed on preformed and hardened selections of Ovako 677 (Ovatec 677) with external turning with continuous operation and a starting diameter of 108 mm. The workpieces have a conical flank, which results in a constant machining time even if the diameter decreases with each workpiece pass. Hardening was performed at 900 °C for 20 minutes after heating. Cooling was performed in air. Tempering at 150 °C for 90 minutes was performed within 20 hours after hardening. The hardness has a uniform distribution of 60-61 HRc in the test section.
[0014] The chemical composition of the material Ovako 677 according to the manufacturer is given in Table 5. The remainder is iron. Briefly, it is 67CrSi4. [Table 5] Cutting parameters were 170 m / min, 0.15 mm / rev, 0.15 mm, dry cutting. Machining time was 32 seconds per workpiece pass. Surface finish measurements were taken after the 1st, 3rd, 7th and 15th workpiece pass. Alicona images were generated after the 1st and every 2nd workpiece pass thereafter. There were a maximum of 15 workpiece passes. Tool life diagnostic criteria were chipping or fracture. The test matrix can be seen in Table 6. [Table 6] The surface feature data from both Figures 29 and 30, combined with the wear analysis of the images in Figure 31, showed that from a tool life perspective, Z11 gave the best results. From a purely surface finish perspective, both the V2 and DSC500 gave better surface finish than Z11 until edge damage became so severe that the test was stopped after 9 workpiece passes (288 seconds of machining time). Figure 32a-c shows very similar wear patterns at the end of tool life between edge 1 and edge 2 of each grade. The biggest difference between edges 1 and 2 of Z11 was that edge 1 had made 9 workpiece passes and edge 2 had made 15 workpiece passes, thereby showing the same type of wear that was greater than the first.
[0015] Microstructural analysis Closer examination of the microstructure reveals the presence of specific precipitates in the binder microstructure, which can be characterized as being substantially spherical, platelet-like, or needle-like. These are summarized in Table 7. [Table 7] The legend for Table 7 is provided with reference to Figure 8. Figure 8a shows typical A1 features; Figure 8b shows typical A2 features; Figure 8c shows typical N1 features; Figure 8d shows typical N2 features; and Figure 8e shows typical N3 features. Additional test samples were produced under similar high pressure temperature conditions, specifically at about 1800°C and 8 GPa. Figures 33 through 36 show the rounded solid solution precipitates typically found in V2, and similarly, Figure 38 shows the rounded solid solution precipitates typically found in Z11. Figure 37 shows the needle-like and platelet-like precipitates typically found in Z1. Evidence of W / Ti precipitates was also observed in some samples. Contamination from the WC grinding media is likely to have affected the binder chemistry to a similar extent. The binder was not free of impurities from the grinding process. The example PCBN materials are characterized by both improved fracture toughness due to the presence of precipitates and significantly better wear resistance compared to the reference material due to solid solution formation, resulting in extended tool life. The PCBN materials described herein may be used as part of a tool for use in applications such as cutting, grinding, grinding, drilling, or other abrasive applications. In summary, the inventors have successfully identified several materials suitable for use in extreme tooling applications that provide effective and attractive alternatives to CRM. In particular, PCBN materials are well suited for turning difficult-to-machine alloys and superalloys and offer many advantages over cemented carbide solutions.
[0016] definition As used herein, "PCBN" refers to a type of superhard material that includes grains of cBN dispersed within a matrix that includes a metal or ceramic. PCBN is an example of a superhard material. As used herein, "matrix material" is understood to mean a matrix material that completely or partially fills the pores, interstices or interstitial areas in the polycrystalline structure. The term "matrix precursor powder" is used to mean a powder that becomes a matrix material when subjected to a high pressure, high temperature sintering process. A multimodal grain size distribution of a large amount of grains is understood to mean grains having a grain size distribution with two or more peaks, each peak corresponding to a respective "mode". A multimodal polycrystalline body may be made by providing a plurality of grains of two or more origins, each origin comprising grains having a substantially different average grain size, and mixing grains or particles from the origins together. In one embodiment, the PCBN material may include cBN grains having a multimodal distribution.
[0017] The claims refer to the average particle size, which is measured using the Equivalent Circular Diameter (ECD) technique. The ECD distribution of a plurality of loose, unbound, non-agglomerated particles can be measured by laser diffraction, where the particles are randomly positioned in the path of an incident light beam, and the diffraction pattern resulting from the diffraction of the light by the particles is measured. The diffraction pattern is mathematically interpreted as if it were produced by a plurality of spherical particles, and the diameter distribution is calculated and reported in terms of ECD. The interpretation of the particle size distribution can be expressed in terms of various statistical properties using various terms and symbols. Specific examples of such terms include the mean, median, and mode. The particle size distribution can be considered as a set of values Di corresponding to each of a set of size channels, where each Di is the geometric mean ECD value corresponding to a respective channel i, where i is an integer ranging from 1 to the number of channels used, n.
[0018] Although the present invention has been shown and described in detail with reference to illustrative embodiments, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the scope of the invention as defined in the appended claims. Yet another aspect of the present invention may be as follows. [1] A polycrystalline cubic boron nitride (PCBN) material, 30-90% by volume of cubic boron nitride (cBN) particles; a matrix material having the cBN particles dispersed therein, the matrix material having a content of 10% by volume to 70% by volume of the PCBN material; The matrix material comprises a titanium compound, an aluminum compound, or a mixture thereof; the matrix material further comprises precipitates and / or grains comprising zirconium and / or vanadium, and optionally tungsten and / or titanium; the precipitates and / or grains have a shape that is either substantially spherical, platelet-like, or needle-like; The PCBN material, wherein the precipitates and / or grains have an average maximum linear dimension of 1 μm or less. [2] The PCBN material according to [1] above, wherein the precipitates and / or grains include nitrides, carbides, carbonitrides and / or diborides. [3] The PCBN material according to [1] or [2] above, wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains are contained in an amount of 10 volume % to 25 volume % of the PCBN material. [4] The PCBN material according to [1], [2] or [3], wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains are contained in an amount of 10 volume %, 17.5 volume %, or 25 volume % of the PCBN material. [5] The PCBN material according to any one of the above [1] to [4], wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains have an average maximum linear dimension of 0.50 μm or less. [6] The PCBN material according to any one of the above [1] to [5], wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains have an average maximum linear dimension of 0.20 μm or less. [7] The PCBN material according to any one of [1] to [6] above, wherein the matrix material contains any one of titanium carbonitride, titanium carbide, titanium nitride, titanium diboride, aluminum nitride, and aluminum oxide. [8] The PCBN material according to [7] above, containing 10 volume % to 25 volume % of titanium carbide (TiC) or titanium nitride (TiN). [9] The PCBN material according to any one of the above [1] to [8], further comprising 5 volume % of aluminum (Al) or a compound thereof.
[10] The PCBN material according to any one of [1] to [9] above, containing 60 volume % of cubic boron nitride (cBN).
[11] The PCBN material according to any one of [1] to
[10] above, wherein the cBN particles have an average size of 0.5 μm to 15 μm.
[12] The PCBN material according to any one of the above [1] to
[11] , wherein the PCBN material has a Vickers microhardness of 26 GPa to 34 GPa.
[13] A method for producing a polycrystalline cubic boron nitride (PCBN) material, comprising: grinding together the following precursor powders: Cubic boron nitride (cBN), vanadium-containing powder and / or zirconium-containing powder, and Powder containing either aluminum or titanium; compressing the milled precursor powder to form a green compact; sintering the green compact at a temperature of 1800°C to 2300°C and a pressure of 7.0 GPa to 8.5 GPa to form a sintered PCBN material; 1. A method according to claim 1, wherein the PCBN material comprises particles of cubic boron nitride (cBN) dispersed in a matrix material comprising zirconium and / or vanadium, and optionally tungsten and / or titanium-containing precipitates and / or grains, the precipitates and / or grains having an average maximum linear dimension of 1 μm or less.
[14] The method according to
[13] above, wherein the temperature is 1800°C to 1900°C.
[15] The method for producing a PCBN material according to
[13] or
[14] , wherein the step of grinding the precursor powders together includes the following two substeps: milling the vanadium-containing powder and / or the zirconium-containing powder for a period of time; adding the powder of cubic boron nitride and an aluminum and / or titanium containing powder; Milling all of the precursor powders together for an additional period of time.
[16] The method for producing a PCBN material according to
[13] ,
[14] or
[15] , further comprising a step of dividing the green compact into several parts prior to the sintering step.
[17] A tool comprising the PCBN material according to any one of [1] to
[12] above.
[18] The tool according to
[17] above, which is a tool for cutting, turning, grinding, grinding, drilling, or other abrasive applications.
Claims
1. 1. A polycrystalline cubic boron nitride (PCBN) material, comprising: 30-90 volume % cubic boron nitride (cBN) particles; a matrix material having the cBN particles dispersed therein, the matrix material content being 10% to 70% by volume of the PCBN material; The matrix material comprises a titanium compound, an aluminum compound, or a mixture thereof; the matrix material further comprises precipitates and / or grains comprising zirconium and / or vanadium, and optionally tungsten and / or titanium; the precipitates and / or grains have a shape that is substantially spherical; A PCBN material, wherein said precipitates and / or grains have an average maximum linear dimension of 1 μm or less.
2. 2. The PCBN material of claim 1, wherein the precipitates and / or grains comprise nitrides, carbides, carbonitrides and / or diborides.
3. 3. The PCBN material of claim 1 or 2, wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains comprise 10% to 25% by volume of the PCBN material.
4. 4. The PCBN material of claim 1, 2 or 3, wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains comprise 10%, 17.5%, or 25% by volume of the PCBN material.
5. The PCBN material of any one of claims 1 to 4, wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains have an average maximum linear dimension of less than or equal to 0.50 µm.
6. The PCBN material of any one of claims 1 to 5, wherein the zirconium-containing precipitates and / or grains, and / or the vanadium-containing precipitates and / or grains have an average maximum linear dimension of less than or equal to 0.20 µm.
7. The PCBN material according to any one of claims 1 to 6, wherein the matrix material comprises any one of titanium carbonitride, titanium carbide, titanium nitride, titanium diboride, aluminium nitride and aluminium oxide.
8. 8. The PCBN material of claim 7, comprising 10% to 25% by volume of titanium carbide (TiC) or titanium nitride (TiN).
9. 9. The PCBN material of claim 1, further comprising 5% by volume of aluminium (Al), or a compound thereof.
10. 10. The PCBN material of any one of claims 1 to 9, comprising 60% by volume of cubic boron nitride (cBN).
11. The PCBN material according to any one of claims 1 to 10, wherein the cBN particles have an average size of 0.5 µm to 15 µm.
12. The PCBN material according to any one of the preceding claims, wherein the PCBN material has a Vickers microhardness of between 26 GPa and 34 GPa.
13. 1. A method for producing polycrystalline cubic boron nitride (PCBN) material, comprising: grinding together the following precursor powders: cubic boron nitride (cBN), vanadium-containing powder and / or zirconium-containing powder, and A powder containing any one of aluminum and titanium; compressing the milled precursor powder to form a green compact; sintering the green compact at a temperature of 1800° C. to 2300° C. and a pressure of 7.0 GPa to 8.5 GPa to form a sintered PCBN material; 13. A method according to claim 12, wherein the PCBN material comprises particles of cubic boron nitride (cBN) dispersed in a matrix material comprising zirconium and / or vanadium, and optionally tungsten and / or titanium-containing precipitates and / or grains, the precipitates and / or grains having an average maximum linear dimension of 1 μm or less.
14. The method of claim 13, wherein the temperature is between 1800°C and 1900°C.
15. 15. The method of claim 13 or 14, wherein the step of grinding the precursor powders together comprises the following two sub-steps: milling the vanadium-containing powder and / or the zirconium-containing powder for a period of time; adding the powder of cubic boron nitride and an aluminum and / or titanium containing powder; Milling all of the precursor powders together for an additional period of time.
16. 16. A method for producing a PCBN material according to claim 13, 14 or 15, further comprising the step of dividing the green compact into portions prior to the sintering step.
17. A tool comprising the PCBN material of any one of claims 1 to 12.
18. 20. The tool of claim 17, which is a tool for cutting, turning, milling, grinding, drilling, or other abrasive applications.
Citation Information
Patent Citations
Cubic boron nitride sintered body and cutting tool using the same
JP2008517860A
Composite sintered compact
JP2011207689A
Composite molded articles formed from ceramics and low-volume cubic boronitrides, and production methods.
JP2014520063A
Sintered body and cutting tool
WO2016194416A1
Sintered body and cutting tool including same
WO2019087481A1